P-109 A RETROSPECTIVE AUDIT OF THE DEPARTMENTAL USE OF PROPHYLACTIC ANTIBIOTICS IN ELECTIVE VENTRAL HERNIA SURGERY AS COMPARED TO NATIONAL AND INTERNATIONAL GUIDELINES. (13th October 2022) - Islam, R; Sriskanthanathan, A; Maynard, O; Abdalla, S
Abstract: The routine use of prophylactic antibiotics for the prevention of surgical site infection is no longer recommended in all types of elective ventral hernia repairs, according to national and international guidelines.NICE recommends that prophylactic antibiotics are given only in clean surgeries that involve the use of a prothesis or implant. The British Hernia Society and European Hernia Society state that there is no indication for antibiotic prophylaxis in both open and laparoscopic elective groin hernia repairs with mesh in patients that are healthy and considered low risk for surgical site infection. This is a retrospective audit of patients who underwent elective ventral hernia repairs at Ealing Hospital between June 2021 and December 2021 to assess the compliance of antibiotic prophylaxis with the current guidelines. Forty-nine patients underwent elective ventral hernia repair, of which 44 was with the use of a mesh.Thirty-five of these cases (79.5%) received prophylactic antibiotics. All cases that underwent laparoscopic hernia repair received prophylactic antibiotics. Five cases underwent an elective open ventral hernia repair without a mesh.Three cases who were considered low risk received prophylactic antibiotics. In conclusion, majority of patients along with those who were considered high risk received prophylactic antibiotics, which is compliant with guidelines. However, patients who did not have a mesh repair, or were not considered high risk also received prophylactic antibiotics.It would be useful to improve the awareness of the guidelines by creating clear local guidelines and improving documentation of reasons to give antibiotics against the recommendations.